2022
DOI: 10.20945/2359-3997000000443
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of hormone levels, biomarkers of cellular injury and oxidative stress in multi-stressor military field training exercises

Abstract: The fundamental objective of military field training exercises (FTX) is to prepare military personnel for real-life operations through simulated scenarios. These training sessions often require extreme physical efforts with prolonged, high-intensity exercises that can be combined with food restrictions and partial, or total, sleep deprivation. Such conditions can compromise an individual's physical performance and cause tissue damage, thus affecting their health. This study aimed to perform a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(84 reference statements)
0
2
1
Order By: Relevance
“…In contrast, Serpell and colleagues (2019) did not find any significant correlations between assessed sleep parameters and general daily muscle soreness-a measure of physical strain and potential proxy into developing injury-across 6 weeks of training in professional rugby athletes [24]. However, this study did demonstrate adverse effects of poor sleep health characteristics on hormones that play central roles in musculoskeletal growth and repair, including testosterone and cortisol [23,29]. This finding aligns with the work of Swinbourne and colleagues (2018) that evidenced a decrease in mean cortisol levels following a sleep extension intervention in professional rugby players [28•].…”
Section: Physical Injury: Prevention and Recoverycontrasting
confidence: 58%
“…In contrast, Serpell and colleagues (2019) did not find any significant correlations between assessed sleep parameters and general daily muscle soreness-a measure of physical strain and potential proxy into developing injury-across 6 weeks of training in professional rugby athletes [24]. However, this study did demonstrate adverse effects of poor sleep health characteristics on hormones that play central roles in musculoskeletal growth and repair, including testosterone and cortisol [23,29]. This finding aligns with the work of Swinbourne and colleagues (2018) that evidenced a decrease in mean cortisol levels following a sleep extension intervention in professional rugby players [28•].…”
Section: Physical Injury: Prevention and Recoverycontrasting
confidence: 58%
“…Military training is well known to induce high levels of physical and mental stress in response to great physical exertion, sleep deprivation, and food restriction (26). This type of training could negatively affect hormonal modulation, muscle damage, oxidative stress markers (7,20), and, consequently, physical and cognitive performance (26,43). Therefore, subject evaluation to determine the ideal recovery period is essential to understand the magnitude of the impact of training, improve performance, and preserve the health of military personnel (4,33,35).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our group showed acute reductions in certain body composition variables and a slow return to baseline values in response to search, rescue, and survival training (SRST) (4), and there is a gap in the literature regarding studies evaluating biochemical and hormonal markers in response to military physical training involving sleep and food restriction (7). Considering that there are inconsistencies in the modulation of some hormones (13,16), as well as conflicting results for the alterations in oxidative stress markers and antioxidant capacity (20,41), more studies are needed to understand these changes in this population.…”
Section: Introductionmentioning
confidence: 99%